The impact of firms’ and CEOs’ social media usage on corporate performance - Wafa Ghardallou (Investment Management & Financial Innovations, 2021)
The impact of social media usage on corporate performance has not been examined in the Saudi context. This paper aims to investigate the influence of social media, namely companies’ and CEOs’ involvement in Twitter and LinkedIn, on the profitability of Saudi Arabia listed firms. A dynamic panel estimation method is used to empirically assess this relationship. The study employs 120 firms listed on the Saudi Stock Exchange Tadawul from 2014 to 2017. Data are obtained from the companies’ annual reports. Statements of financial status as well as income statements are used to collect data on the dependent variable and control variables. The results show that having a LinkedIn official account by both the CEO and the company does not improve the enterprise performance. In contrast, companies that are active on Twitter will contribute to an increase in their short-term performance. CEOs who engage in Twitter via a high number of followers help to boost the performance of their companies in the long and short term. Hence, this paper recommends that Saudi firms should be aware that their performance could be increased by monitoring their presence on social networks and by having a strong intention to use these tools. AcknowledgmentsThis study was funded by the Deanship of Scientific Research at Princess Nourah bint Abdulrahman University through the Fast-track Research Funding Program.